ANALISIS KETERLAMBATAN DISTRUBUSI REKAM MEDIS POLI PENYAKIT DALAM DI RST TK.III DR. REKSODIWIRYO PADANG BERDASARKAN METODE FISHBONE - Handam Dewi, Siti; Rahmadhani, Rahmadhani; Mardiawati, Dewi; Maisa Putra, Deni; Wisandra, Ade; Sopiana, Nela (Ensiklopedia of Journal, 2025)
Good distribution of medical record files is the distribution of medical record files that is fast, precise, and efficient. One of the problems found in 5 (five) internal medicine polyclinics that have the most patients and often experience delays in file delivery resulting in missed files (layout). The purpose of this study is to analyze the delay in distributing medical records in internal medicine polyclinics using the fishbone method in kindergarten hospitals. III. Dr. Reksodiwiryo Padang. The type of research used is qualitative with a descriptive approach. This research was conducted at the Kindergarten Hospital. III. Dr. Reksodiwiryo Padang in February-June. The informants in the study amounted to 8 (eight) people with data collection techniques using interview, observation and documentation guidelines. Data processing using the triangulation method with collazzi data analysis.The results of the study were obtained from the fishbone method, namely from Man There are still officers who experience delays in the delivery of files. Money was not found to have any financial problems. Methode does not have an SOP on distribution. Machines and materials were not found to be a problem because they were sufficient. Based on the results of the study, it can be concluded that there are still obstacles, namely that there are still officers who experience delays in distributing files, and there is no SOP regarding distribution. It is hoped that hospitals will immediately make SOPs regarding distribution and overcome problems with delays in the delivery of medical record files. Keywords: Delay,distribusi,medical records